Respuesta :
Answer:
1)
- 6w -33 = 3(4w - 5)
- 6w - 33 = 12w - 15
- 12w - 6w = 15 - 33
- 6w = -18
- w = -18/6
- w = -3
2)
- 6(x + 5) = 3x
- 6x + 30 = 3x
- 6x - 3x = -30
- 3x = -30
- x = -30/3
- x = -10
3)
- (q + 1)/2 = (q - 1)/3
- 3(q + 1) = 2(q - 1)
- 3q + 3 = 2q - 2
- 3q - 2q = -2 - 3
- q = -5
#1
[tex]\\ \sf\bull\longmapsto 6w-33=3(4w-5)[/tex]
[tex]\\ \sf\bull\longmapsto 6w-33=12w-15[/tex]
[tex]\\ \sf\bull\longmapsto 6w-12w=-15+33[/tex]
[tex]\\ \sf\bull\longmapsto -6w=18[/tex]
[tex]\\ \sf\bull\longmapsto w=-3[/tex]
#2
[tex]\\ \sf\bull\longmapsto 6(x+5)=3x[/tex]
[tex]\\ \sf\bull\longmapsto 6x+30=3x[/tex]
[tex]\\ \sf\bull\longmapsto 3x=30[/tex]
[tex]\\ \sf\bull\longmapsto x=10[/tex]
#3
[tex]\\ \sf\bull\longmapsto q+\dfrac{1}{2}=q-\dfrac{1}{3}[/tex]
It has no solutions
[tex]\\ \sf\bull\longmapsto q=\infty[/tex]